Development of a novel electrochemical system for oxygen control (ESOC) to examine dissolved oxygen inhibition on algal activity. Issue 9 (1st July 2013) - Keymer, Philip C.; Pratt, Steven; Lant, Paul A.
ABSTRACT The development of an Electrochemical System for Oxygen Control (ESOC) for examining algal photosynthetic activity as a function of dissolved oxygen (DO) is outlined. The main innovation of the tool is coulombic titration in order to balance the electrochemical reduction of oxygen with the oxygen input to achieve a steady DO set‐point. ESOC allows quantification of algal oxygen production whilst simultaneously maintaining a desired DO concentration. The tool was validated abiotically by comparison with a mass transfer approach for quantifying oxygenation. It was then applied to quantify oxygen inhibition of algal activity. Five experiments, using an enriched culture of Scenedesmus sp. as the inoculum, are presented. For each experiment, ESOC was used to quantify algal activity at a series of DO set‐points. In all experiments substantial oxygen inhibition was observed at DO <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg276wf5wp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />>30 mgO2 L−1</alternatives>. Inhibition was shown to fit a Hill inhibition model, with a common Hill coefficient of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg276wf5zs" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.22±0.07 L mg−1</alternatives> and common log10 CI50 of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg276wf61d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />27.2±0.7 mg L−1</alternatives>. This is the first time that the oxygen inhibition kinetic parameters have been quantified under controlled DO conditions. Biotechnol. Bioeng. 2013; 110:2405–2411. © 2013 Wiley Periodicals, Inc.